2018
DOI: 10.1038/s41598-018-32904-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and co-expression networks reveal tissue-specific responses and regulatory hubs under mild and severe drought in papaya (Carica papaya L.)

Abstract: Plants respond to drought stress through the ABA dependent and independent pathways, which in turn modulate transcriptional regulatory hubs. Here, we employed Illumina RNA-Seq to analyze a total of 18 cDNA libraries from leaves, sap, and roots of papaya plants under drought stress. Reference and de novo transcriptomic analyses identified 8,549 and 6,089 drought-responsive genes and unigenes, respectively. Core sets of 6 and 34 genes were simultaneously up- or down-regulated, respectively, in all stressed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…To explore the expression level characteristics of SR genes under different abiotic stresses in different tissues, we obtained the expression level data of the poplar and papaya SR genes from RNA-seq data [34,35], and Arabidopsis and grape chip data GSE5620, GSE5621, GSE5623, GSE5624, GSE5628 and GSE31594 were obtained from the NCBI GEO database. The log2-transformed fold-change values were used for creating the heatmap.…”
Section: Expression Pattern Analysis Of Sr Genes In Poplar Arabidopsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the expression level characteristics of SR genes under different abiotic stresses in different tissues, we obtained the expression level data of the poplar and papaya SR genes from RNA-seq data [34,35], and Arabidopsis and grape chip data GSE5620, GSE5621, GSE5623, GSE5624, GSE5628 and GSE31594 were obtained from the NCBI GEO database. The log2-transformed fold-change values were used for creating the heatmap.…”
Section: Expression Pattern Analysis Of Sr Genes In Poplar Arabidopsmentioning
confidence: 99%
“…Since abiotic stress may adversely affect plant growth and development, stresstolerant gene studies of plants are important. We obtained microarray (Arabidopsis and grape) and RNA-seq (poplar and papaya) data under various stress conditions from different tissues of the four dicots [34,35]. The results showed that only the CpRSZ20 gene was not expressed, and the rest were expressed (Figure 7).…”
Section: Expression Pattern Analysis Of Sr Genes In Poplar Arabidopsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloned gl14 gene was confirmed responsible for epicuticular wax biogenesis. Through co-expression network analysis, Gamboa-Tuz [ 38 ] also identified several abiotic stress-related hub genes in papaya from roots and leaves under drought stress. However, WGCNA has not been adapted to systematically research hub genes correlated with drought stress in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of high-throughput sequencing technology and bioinformatics, tissue-specific gene expression and regulation analyses have been carried out on many crops [9][10][11]. In particular, weighted gene coexpression network analysis (WGCNA) has recently been widely used to predict the functional roles of gene coexpression modules and individual genes underlying the differences between tissues [12][13][14]. For example, WGCNA or comparative transcriptomic analysis revealed coexpression modules and dynamics in gene expression involved in stress response [12], seed development [13], and floral bud development [14] in various tissues of crop plants, etc.. WGCNA has become a fascinating integrated and systematic genome-wide approach, focusing on elucidating biological networks and gene function [15].…”
Section: Introductionmentioning
confidence: 99%